Ethical Communication as a Key Element of Corporate Social Responsibility - Aleksandra KUZIOR; Anna KOCHMAŃSKA; Izabela MARSZAŁEK-KOTZUR (Communications of International Proceedings, 2021)
Corporate social responsibility is an important factor in building a climate of cooperation between business and the broadly understood group of stakeholders, i.e. employees, local community, suppliers, customers and contractors. This climate is based on mutual respect and refraining from overexploitation of human, environmental and other resources. One of the elements of corporate social responsibility is interpersonal communication. It seems to occupy a key position in building the strategy and culture of enterprises. The article is theoretical and presents philosophical analyses of the essence of ethical communication. It is an attempt to reflect on selected aspects of correct communication in a difficult, full of changes, technological reality.
Keywords: Responsibility; Ethics; Business; Communication